About tax psychology (Journal of Economic Research & Business Administration, 2016)
Continuous and massive reforming of tax system in Republic of Kazakhstan in modern stage needs in analyses and the understanding psychological factors, impacting to this process. For achievement the country’s investment attractiveness and quality taxpayer service is need to change not only tax legislation also the tax culture society. This long process requires a gradual change of the moral values of society, adequate changes of tax mentality, elimination of adverse circumstances and reasons. Using the psychological methods and knowledge for the supporting this normal process is allowed to improve gradually not only the public service and also team’s work of the public officers, to reduce losing of taxpayer and create the favorable conditions. Problem formation of business and population a sense of responsibility in the discharge of tax liability requires new measures, and including psychological, to help to get the taxpayer that government revenues needed to provide by its government of public services in the trust field.
Keywords: tax psychology; tax morale; tax mentality; tax burden; behavior correction; tax liability; communication model; motivation method; reliance; a sign of freedom.